Retreival of a migrated and incorporated lumen apposing metal stent from pancreatic body using laparoscopic technique alone - Reddy, Hetish M.; Bagree, Rajendra; Gaurav, Subhanshu; Imam, Syed Gazanfar; Panwar, Pradeep (International Surgery Journal, 2019)
Endoscopic or endoscopic ultrasound-guided drainage (EUS-GD) has become the mainstay of treatment for symptomatic pancreatic fluid collections. Various plastic or metal stents are available to facilitate drainage, amongst which lumen apposing metal stent (LAMS) has better efficacy and fewer complications in comparison with others. Though most drainage related complications can be managed non-operatively, stent related complications like stent migration may sometimes require a surgical retrieval. The longer the observation period, the harder the retrieval in rare cases wherein the LAMS migrates and incorporates in the retroperitoneum. When endoscopic retrieval is not an option, laparoscopic approach might be considered as an alternative to open surgery. We report a case of successful laparoscopic retrieval of a LAMS, 5 months after its migration and getting incorporated in the pancreatic head, without endoscopic assistance.